Effectiveness of Autologous Platelet Concentrates in Management of Young Immature Necrotic Permanent Teeth—A Systematic Review and Meta-Analysis - Panda, Saurav (Cells, 2020)
The use of autologous platelet concentrates (APCs) in regenerative endodontic procedures is inconsistent and unclear. The aim of this meta-analysis was to evaluate the effectiveness of autologous platelet concentrates compared to traditional blood-clot regeneration for the management of young, immature, necrotic, permanent teeth. The digital databases MEDLINE, SCOPUS, CENTRAL, Web of Science, and EMBASE were searched to identify ten randomized clinical trials. The outcomes at postoperative follow-up, such as dentinal wall thickness (DWT), increase in root length (RL), calcific barrier formation (CB), apical closure (AC), vitality response (VR), and success rate (SR), were subjected to both qualitative synthesis and quantitative meta-analysis. The meta-analysis showed that APCs significantly improved apical closure (risk ratio (RR) = 1.17; 95% CI: 1.01, 1.37; p = 0.04) and response to vitality pulp tests (RR = 1.61; 95% CI: 1.03, 2.52; p = 0.04), whereas no significant effect was observed on root lengthening, dentin wall thickness, or success rate of immature, necrotic teeth treated with regenerative endodontics. APCs could be beneficial when treating young, immature, necrotic, permanent teeth regarding better apical closure and improved response to vitality tests.